Analisis Arus Kas dalam Menilai Kinerja Keuangan pada PT. Telkom Indonesia (Persero) Tbk Tahun 2019-2023 - Rivan Syarif Kaisar; Siti Hasbiah; Nurman Nurman; Romansyah Sahabuddin; Anwar Anwar (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
The study aims to determine how the financial performance of PT. Telkom Indonesia (Persero) Tbk is when assessed using cash flow statements and cash flow ratios. Data collection was carried out using Library research techniques and documentation. The population in this study is the 2019-2023 financial statements of PT. Telkom Indonesia (Persero) Tbk. The entire population in this study is also a sample. The research method uses descriptive analysis using cash flow from operating activities, investment, and financing as well as ratio analysis, namely the Operating Cash Flow ratio (AKO), Fund Flow Coverage Ratio (CAD), Cash Flow Coverage Ratio to Interest (CKB), Cash Coverage Ratio to Current Liabilities (CKHL), Capital Expenditure Ratio (PM), and Cash Flow Adequacy Ratio (KAK). The results of this study show that the amount of the company's cash flow during the 2019-2023 period shows that the company is in a liquid condition when assessed in terms of its operational activities. With the ratio analysis that has been done, it can be concluded that there is an increase in cash flow, especially in operating activities each year and the company's ability to overcome its current liabilities can still be overcome. This shows that PT. Telkom Indonesia (Persero) Tbk is in a fairly good position during the 2019-2023 period.